A complete guide to human microbiomes: Body niches, transmission, development, dysbiosis, and restoration - Reynoso-García, Jelissa; Miranda-Santiago, Angel E.; Meléndez-Vázquez, Natalie M.; Acosta-Pagán, Kimil; Sánchez-Rosado, Mitchell; Díaz-Rivera, Jennifer; Rosado-Quiñones, Angélica M.; Acevedo-Márquez, Luis; Cruz-Roldán, Lorna; Tosado-Rodríguez, Eduardo L.; Figueroa-Gispert, María Del Mar; Godoy-Vitorino, Filipa (Frontiers in Systems Biology, 2022)
Humans are supra-organisms co-evolved with microbial communities (Prokaryotic and Eukaryotic), named the microbiome. These microbiomes supply essential ecosystem services that play critical roles in human health. A loss of indigenous microbes through modern lifestyles leads to microbial extinctions, associated with many diseases and epidemics. This narrative review conforms a complete guide to the human holobiont - comprising the host and all its symbiont populations- summarizes the latest and most significant research findings in human microbiome. It pretends to be a comprehensive resource in the field, describing all human body niches and their dominant microbial taxa while discussing common perturbations on microbial homeostasis, impacts of urbanization and restoration and humanitarian efforts to preserve good microbes from extinction.